2019
DOI: 10.1038/s41598-019-43587-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the decision making chemicals used for bacterial growth

Abstract: Predicting the contribution of media components to bacterial growth was first initiated by introducing machine learning to high-throughput growth assays. A total of 1336 temporal growth records corresponding to 225 different media, which were composed of 13 chemical components, were generated. The growth rate and saturated density of each growth curve were automatically calculated with the newly developed data processing program. To identify the decision making factors related to growth among the 13 chemicals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…However, the participation of components other than the target component in adaptive evolution has generally been neglected. A machine learning analysis of medium components showed that it was the trace elements (e.g., metal ions) rather than the major nutrients (e.g., glucose) that determined bacterial growth, which was sensitive to the concentration gradient ( Ashino et al, 2019 ). Thus, whether and how adaptation through experimental evolution is associated with correlated adaptation to environmental gradients must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the participation of components other than the target component in adaptive evolution has generally been neglected. A machine learning analysis of medium components showed that it was the trace elements (e.g., metal ions) rather than the major nutrients (e.g., glucose) that determined bacterial growth, which was sensitive to the concentration gradient ( Ashino et al, 2019 ). Thus, whether and how adaptation through experimental evolution is associated with correlated adaptation to environmental gradients must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of a growth curve is unpredictable, even for defined strains growing under well-controlled conditions in the laboratory, because bacterial growth is attributed to not only the genotype but also the external factors, such as the composition of the medium. Our previous findings 2 of 11 verified that bacterial growth was either coordinated with genome reduction [14,15] or determined by the chemical composition of the growth medium [16]. Thus, model-based growth analyses were unsuitable to create a linkage between the growth dynamics and the growth condition.…”
Section: Introductionmentioning
confidence: 92%
“…The stock solutions, that is, 1 M glucose, 0.615 M K2HPO4, 0.382 M KH2PO4, 0.203 M MgSO4, 0.0152 M thiamin/HCl, 0.0018 M FeSO4, and 0.766 M (NH4)2SO4, were sterilized using a sterile syringe filter with a 0.22-µm pore size hydrophilic PVDF membrane (Merck). The concentrations of most chemical compounds were altered one-by-one on a logarithmic scale to achieve a wide range of environmental gradients, as described previously 25 , which led to a total of alternative medium combinations (C1~28) were used for the fitness assay. The resultant concentrations of individual components in the ionic form are summarized in Table S2.…”
Section: Media Combinationsmentioning
confidence: 99%